2014
DOI: 10.1002/er.3186
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light response photocatalytic water splitting over CdS/TiO2and CdS-TiO2/metalosilicate composites

Abstract: SUMMARY In this work, we have synthesized two different phases of CdS nanoparticles, CdS/TiO2 composites and their supported form on ZSM‐5 type metalosilicates (ferrisilicate and aluminosilicate) as CdS–TiO2/metalosilicate composites. The photocatalytic performance of these samples was evaluated by monitoring the amount of hydrogen evolved from water under visible‐light irradiation. The supported composites of TiO2–CdS/metalosilicate exhibited a higher photocatalytic activity in the photocatalytic water splitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…As shown in Figure 6, both of them belong to H4 type IV with a hysteresis loop. The hysteresis loop of F-TiO2 occurs at the relative pressure of 0.20 and that of 1% CdS/F-TiO2 occurs at the relative pressure of 0.40, which indicates that the pore structure of the sample is irregular, mainly the mixture of micropores and mesopores and the narrow fracture pore [26,27]. It can be seen from the pore size distribution diagram that the pore size distribution of Figure 6a is not uniform and the number of pores is very small, which can be ignored basically.…”
Section: Bet Analysismentioning
confidence: 99%
“…As shown in Figure 6, both of them belong to H4 type IV with a hysteresis loop. The hysteresis loop of F-TiO2 occurs at the relative pressure of 0.20 and that of 1% CdS/F-TiO2 occurs at the relative pressure of 0.40, which indicates that the pore structure of the sample is irregular, mainly the mixture of micropores and mesopores and the narrow fracture pore [26,27]. It can be seen from the pore size distribution diagram that the pore size distribution of Figure 6a is not uniform and the number of pores is very small, which can be ignored basically.…”
Section: Bet Analysismentioning
confidence: 99%
“…In this case, the absorbed H + on the surface of film and Cu + in film may be reduced by the photogenerated electrons. Although the reduction of Cu + to metallic copper is thermodynamically favorable than the reduction of H + because of a higher overpotential according to Equations (2) and (4), the metallic copper inclusions in the film impede the forward reaction of Equation (4). Meanwhile, the metallic copper inclusions as good electrical conductor facilitate the transportation of photogenerated electrons from the bulk to the film/solution interface to reduce the H + .…”
Section: Mechanism Of the Improved Photoelectrochemical Stability Of mentioning
confidence: 99%
“…The materials of photoelectrodes play a key role in the PEC hydrogen production. N-type metal oxide semiconductors, such as TiO 2 [2][3][4], α-Fe 2 O 3 [5,6], and SrTiO 3 [7], are usually used as photoanodes to produce hydrogen at counter electrodes, and p-type metal oxide semiconductors, such as Cu 2 O [8][9][10][11][12], CuFeO 2 [13,14], and CuGaO 2 [15], are used as photocathodes to produce hydrogen on them. Although n-type metal oxide semiconductors as photoanodes have been extensively studied, the applications of p-type metal oxide semiconductors have not been reported much [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Because the solar spectrum contains 5% UV light, 48% visible (Vis) light, and 44% near infrared light [5], it is a better option to narrow the wide band gap of metal oxide semiconductors so that one can use Vis light to activate the catalyst. Several methods like successive ionic layer adsorption and reaction (SILAR) [20], surface-functionalized method [21], chemical vapor deposition [22], and metalosilicate support [23] have been tried to produce heterojunctions of TiO 2 /CdS either in the form of thin films or nanoparticles, but most of these methods require the use of high vacuum, multistep/tedious process, production of chemical by-products, and the use of special solvents. Previous reports have shown that better performance is achieved from the use of cadmium sulfide (CdS) [9,10] among all other narrow band gap semiconductors like CuTe [11], PbSe [12], PbS [13], CdSe [14], and InP [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, synthesizing a composite structure of CdS and TiO 2 can produce a symbiotic interaction, which might lead to a more active catalyst with Vis light absorption and reduced photogenerated electron-hole pair migration. Several methods like successive ionic layer adsorption and reaction (SILAR) [20], surface-functionalized method [21], chemical vapor deposition [22], and metalosilicate support [23] have been tried to produce heterojunctions of TiO 2 /CdS either in the form of thin films or nanoparticles, but most of these methods require the use of high vacuum, multistep/tedious process, production of chemical by-products, and the use of special solvents. Based on these facts, a green, fast, and optical technique [24] known as pulsed laser ablation in liquid (PLAL) has been proved very beneficial in synthesizing metal semiconductor nanocrystals such as chalcogenides like CdSe [25] and oxide semiconductors like TiO 2 [26,27], CuO [28,29], and ZnO [30,31].…”
Section: Introductionmentioning
confidence: 99%